Features of the sea ice cover variability in the Tatar Strait (Japan Sea) in connection with the regional atmosphere circulation - Irina L. Tsypysheva; Larisa S. Muktepavel; G. Sh. Tsitsiashvili; Tatyana A. Shatilina; Tatyana V. Radchenkova (Известия ТИНРО, 2016)
Variations of the sea ice cover in the Tatar Strait (Japan Sea) in 1951-2014 are analyzed in connection with changes of surface atmospheric pressure, geopotential height H500, and air temperature over eastern Asia and the North-West Pacific. Besides, water circulation and spatial distribution of the sea ice and water temperature in the southern Tatar Strait are described in detail for March of 2014 and 2015 using satellite data (MODIS/Terra, MODIS/Aqua, MTSAT1). Dominant periodicities are revealed for the whole time series of ice cover and its parts (1951-1982 and 1983-2014): the 5-year cycle dominated in January-March for the former period, and the 2-year cycle - for the latter period, whereas long-term cycles (7-10 years) were weaker. Significant trend is found for the 1950-1982 but it is not significant for the 1983-2014. The ice cover variation correlated with changes of the Siberian High strength in the 1951-1982 but mostly with atmosphere processes over south Asia and the Okhotsk Sea in the 1983-2014, that’s why the 2-year cycle was stronger in the latter case. Mechanism of «cold» winters formation is considered in detail for a case of 2001, and the mechanism of «warm» winters formation - for the 1991, 2008, 2014, and 2015. Two scenarios are available for the latter case of low ice cover: i) abnormally southern position of the trough on H500 surface over the Okhotsk Sea; and ii) the ridge on H500 surface over the Japan Sea and adjacent continental areas. The ice cover fluctuations in 2015 are forecasted and this forecast comes true for February and March. Features of spatial distribution of the ice, water dynamics and thermal regime are considered in detail for the southern Tatar Strait in March 2014 and 2015 using satellite data.